First and Second Language English Students in Tertiary Education: Reading and Academic Performance - Andor, Karen Erica (My University, 2006)
Previous studies have examined the issue of assessing university students and relating their performance on the assessment measures to their academic performance in South Africa (Butler & Van Dyk, 2004; Nel, Dreyer, & Kopper, 2004). Nel et al (2004) used a comprehensive assessment battery whereas Butler and Van Dyk (2004) used a single test, the ELSA-PLUS. However, there is very little research on the relationship between reading and academic performance (Onwuebuzie, Mayes, Arthur, Johnson, Robinson, Ashe, Elbedous & Collins, 2004). The Stanford Diagnostic Reading Test (SDRT) Blue Level was administered to 380 first year students in the one of the schools in an English medium university in South Africa at the beginning of 2005. 67 students volunteered to have their results used in the study of which 22 were English second language (L2) speakers and 43 were English first language (L1) speakers. The results showed that there were significant differences between the L1 and L2 students, where the performance of the L2 students was significantly weaker than that of the L1 students on the Reading Comprehension, Vocabulary, Word Parts and Structural Analysis subtests of the SDRT. However, it emerged that the SDRT is not a good predictive test for academic achievement for either L1 or L2 students.
Student Number : 9305365T - MEd research report - School of Education - Faculty of Humanities
Keywords: academic performance; english first language; english second language; reading; SDRT; university